Analysis of the Social Value of Friendship in the Novel “5 cm” by Donny Dhirgantoro - Grace Abeliani Saragih; Marudut Bernadtua Simanjuntak (BADAN PENERBIT STIEPARI PRESS, 2022)
5 cm is a novel written by a novelist named Donny Dhirgantoro, this novel tells about the friendship life of five friends who teach a lot about sincerity, care, and sincerity. Not a day without a meeting, and not having other friends by their side until the feeling of saturation approaches. Finally, they agreed to cut off their friendship for 3 months, to find their other lives and pursue a dream that had been delayed. With an agenda, if they meet again later they will carry out a love adventure mission to show the identity of the friendship they are looking for. They face various big obstacles on their mission journey, but they believe this is what strengthens their bond even more. The purpose of the research on the 5 cm novel is to provide an overview of the values of pure friendship contained in their story. In the analysis, the researcher uses qualitative methods, the data in the study is in the form of documents, namely 5 cm novels. The conclusion is that the story of five friends who are looking for their identity without preempting their solidarity, friendship, and dreams will continue to be on their agenda for the rest of their lives